Monoclonal gammopathy of undetermined significance-associated scleromyxoedema - Kalgi D Baxi; Raju G Chaudhary; Santoshdev P Rathod; Ashish Jagati (Wolters Kluwer Medknow Publications, 2019)
Scleromyxoedema is a rare generalized cutaneous mucinosis, which in absence of thyroid disease, occurs almost invariably in patients with monoclonal gammopathies. A 54-year-old female patient presented with complaint of tightening of skin on the extremities, abdomen, forehead, gradually progressive since 1 year, episodes of generalized tonic-clonic convulsions, and acute psychosis since 5 days. Cutaneous examination revealed nonpitting edema over the face and sclerodermoid changes over extremities. Laboratory investigations showed presence of M-band on serum-protein electrophoresis and monoclonal spike of IgG lambda component on immunofixation. Magnetic resonance imaging of the brain showed periventricular subcortical lacunar infarcts. Skin biopsy with mucin staining was suggestive of scleromyxoedema. All other investigations were normal. Bone marrow biopsy showed a mild focal increase in plasma cells. The cutaneous, serological, and electrophoretic findings as well as the clinical profile of the patient were consistent with the diagnosis of monoclonal gammopathy of undetermined significance associated with scleromyxoedema. This case is presented because of its rare occurrence.